ANALYSIS OF THE ROMANCE "KASHMIRDA" BY M.ASHRAFI (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article presents a theoretical analysis of the novel "Kashmirda" by the famous composer Mukhtar Ashrafi. Also, the article examines the application of the styles of this work belonging to the modern composer's creativity.